Peaceful Da’wah and Religious Conflicts in Contemporary Indonesia - Haramain, Muhammad; Aminah, St. (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
At least there are two trends in contemporary da'wah challenges; First, the tendency of some Preachers to be extreme and strict in understanding religious notions (da'wa ethics) and trying to force these ways in delivering da'wah. Second, other tendencies are permissive acts to religious practices and accommodating negative attitudes and thoughts that came from pop culture and modern life. Both of these trends can be observed from the Al-Qur‘an statement about al-guluww fi al-din (excessive attitudes in religion) in Q.S. al-Ma'idah / 5: 77. In a more specific aspect, it can be observed that the university curriculum at the Da'wah Faculties of Indonesian Islamic Universities is still lacking in emphasizing the aspect of peaceful da'wah, especially in the Indonesian perspective. The ideal Da’i (Islamic Preachers) insight is at least not only on normative theological aspects but requires other insights such as world view, human rights, cultural insights and local traditions.